2013
DOI: 10.1073/pnas.1220693110
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of ribonucleotide reductase improves cardiac performance

Abstract: We previously demonstrated that cardiac myosin can use 2-deoxy-ATP (dATP) as an energy substrate, that it enhances contraction and relaxation with minimal effect on calcium-handling properties in vitro, and that contractile enhancement occurs with only minor elevation of cellular [dATP]. Here, we report the effect of chronically enhanced dATP concentration on cardiac function using a transgenic mouse that overexpresses the enzyme ribonucleotide reductase (TgRR), which catalyzes the rate-limiting step in de nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 45 publications
(72 reference statements)
6
43
0
Order By: Relevance
“…This notion is well supported by a number of prior studies showing functional gap junction coupling with fibroblasts[45–48]. In agreement with our previous reports[15,16], this experiment further supports the absence of deleterious effects of dATP on the relaxation kinetics of cardiomyocytes and supports the idea that dATP may represent a way to increase systolic function without impairing diastolic performance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This notion is well supported by a number of prior studies showing functional gap junction coupling with fibroblasts[45–48]. In agreement with our previous reports[15,16], this experiment further supports the absence of deleterious effects of dATP on the relaxation kinetics of cardiomyocytes and supports the idea that dATP may represent a way to increase systolic function without impairing diastolic performance.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous work has shown that R1R2 overexpression results in increased contractility in neonatal and mature adult rat cardiomyocytes[15,16]. We first verified that overexpression of R1R2 results in similar increases in contraction magnitude and velocity in hESC-CMs.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Motivated by this goal, Longyear et al 51 recently demonstrated that replacing ATP with the ATP analog, 2-deoxy-ATP, can significantly attenuate the depressive effects of acidosis on filament velocity and Ca 2+ sensitivity 51 in the in vitro motility assay. Thus, this may represent a promising agent not only to potentially treat chronic heart failure, as is being explored, 62 but also, based on our results, to help attenuate skeletal muscle fatigue. In addition, College of Sports Medicine and permission has been granted for this version to appear in e-Publications@Marquette.…”
Section: Can Fatigue Be Attenuated In Clinical Populations?mentioning
confidence: 86%